Did tuition fees in Germany constrain students' budgets? New evidence from a natural experiment - Stephan Thomsen; Friederike von Haaren-Giebel (IZA Journal of European Labor Studies, 2016)
Less than a decade ago, several German states introduced tuition fees for university education. Despite their comparatively low level of about exteuro500 per semester, fees were perceived by the public to increase social injustice and have been abolished recently. Whereas other studies have shown no effect on enrollment, we analyze the effects on students' budgets. To identify causal effects, we exploited the natural experiment established by the introduction of fees. Tuition fees decrease total expenditure moderately by about 4 %. With regard to financial resources, students are more likely to receive support from parents or take out a loan.
Keywords: I22; I28; H75; 330; Tuition fees; Student spending; Natural experiment; Germany